Routinization, Within-Occupation Task Changes and Long-Run Employment Dynamics - Davide Consoli; Giovanni Marin; Francesco Rentocchini; Francesco Vona (Fondazione Eni Enrico Mattei (FEEM), 2022)
The present study adds to the literature on routinization and employment by capturing within occupation task changes over the period 1980-2010. The main contributions are the measurement of such changes and the combination of two data sources on occupational task content for the United States: the Dictionary of Occupational Titles and the Occupational Information Network. We show that within-occupation reorientation away from routine tasks: i) accounts for 1/3 of the decline in routine-task use; ii) accelerates in the 1990s, decelerates in the 2000s but with significant convergence across occupations; iii) allows workers to escape the employment and wage decline, conditional on the initial level of routine-task intensity. The latter finding suggests that task reorientation is a key channel through which labour markets adapt to various forms of labour-saving technological change.
Keywords: J23; J24; O33; 330; Tasks; Routinization; Technological Change; Employment Dynamics; Race between Technology and Education